Topics in Fluorescence Spectroscopy
DOI: 10.1007/0-306-47058-6_8
|View full text |Cite
|
Sign up to set email alerts
|

Inhomogeneous Broadening of Electronic Spectra of Dye Molecules in Solutions

Abstract: It is well known in spectroscopy of complex organic molecules that the large width of their absorption and emission bands is largely due to the existence of a continuous set of vibrational sublevels in each electronic state. The spectroscopic properties of dye molecules in solution are in addition influenced by the surrounding medium.(1-3) For several decades it had been believed that because of the fast energy exchange between the vibrational sublevels the fluorescence spectrum of organic dye in solution was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
79
0

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(83 citation statements)
references
References 22 publications
(27 reference statements)
1
79
0
Order By: Relevance
“…These results show no noticeable spectral shift in the SPCP versus the free space emission for different polymer film thicknesses. Typically, spectral shifts in chromophore emission are ascribed to the changes in the electronic distribution of the energies of electronic transitions [33]. Since we do not observe any noticeable spectral shifts for the coupled phosphorescence with respect to free space emission, we concluded that the reported observations of SPCP are not due to changes in photophysical properties.…”
Section: Resultsmentioning
confidence: 42%
“…These results show no noticeable spectral shift in the SPCP versus the free space emission for different polymer film thicknesses. Typically, spectral shifts in chromophore emission are ascribed to the changes in the electronic distribution of the energies of electronic transitions [33]. Since we do not observe any noticeable spectral shifts for the coupled phosphorescence with respect to free space emission, we concluded that the reported observations of SPCP are not due to changes in photophysical properties.…”
Section: Resultsmentioning
confidence: 42%
“…The temperature-induced blue shift is well known effect observed for different organic compounds [15][16][17][18][19][20][21][22][23][24]. It is common to represent the spectral properties of such solutions by the energy level diagram of the spectral centre or solvate consisting of the dye and the nearest solvent molecules.…”
Section: Vladimir I Tominmentioning
confidence: 99%
“…Solvatochromic systems are characterised by the next well documented [15][16][17][18][19][20][21][22][23][24] features of the emission bands:…”
Section: Vladimir I Tominmentioning
confidence: 99%
See 2 more Smart Citations